2005
DOI: 10.1016/j.carbon.2004.08.018
|View full text |Cite
|
Sign up to set email alerts
|

XRD and TEM study of high pressure treated single-walled carbon nanotubes and C60-peapods

Abstract: In situ synchrotron X-ray diffraction measurements of single-walled carbon nanotube and C 60 -peapod samples under high pressures up to 13 GPa and at high temperature were carried out. Anisotropical shrinkages of their bundle 2-dimensional lattices by compression at room temperature were observed. It was found that the lattices recover original forms reversibly upon pressure release. It was also found Preprint submitted to Elsevier Science 19 August 2004that irreversible phase transformations occur by raising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 21 publications
5
28
0
Order By: Relevance
“…Since the contribution of the structure factor of C 60 chain inside the tube reduces the total structure factor at the 100 peak position [13], the 100 peak intensity of the C 60 -peapod sample is much lower than that of the SWNT sample, the observed XRD patterns confirmed us that C 60 molecules were As we reported in previous paper [12], diffraction peaks of the c-SWNT sample disappeared above about 2 GPa ( …”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Since the contribution of the structure factor of C 60 chain inside the tube reduces the total structure factor at the 100 peak position [13], the 100 peak intensity of the C 60 -peapod sample is much lower than that of the SWNT sample, the observed XRD patterns confirmed us that C 60 molecules were As we reported in previous paper [12], diffraction peaks of the c-SWNT sample disappeared above about 2 GPa ( …”
Section: Resultssupporting
confidence: 68%
“…Similar polymerization of carbon nanotubes (CNTs) is expected and many high pressure experiments of CNTs have been performed [10][11][12]. However, the detailed structural property of CNTs is still not well understood.…”
Section: Introductionmentioning
confidence: 96%
“…It has been observed that the broader reflection profile results from smaller crystal size [24]. This observation agrees with similar result presented for carbon nanotubes with increasing pressure at room temperature [25].…”
Section: Phase and Structure Of The Productssupporting
confidence: 89%
“…Fig. 3(b) shows the high resolution TEM of the tubes, which exhibit the typical features of multi-walled carbon nanotube [14]. It illustrates that most graphite layer lattice fringes of which are straight, continuous and parallel to the tube axis.…”
Section: Resultsmentioning
confidence: 94%